A model of brand loyalty measurement for islamic banking in Kedah, Pulau Pinang, and Perlis - Wan Omar, Maznah; Mohd Ali, Mohd Noor; Zainal, Noor Saliza; Mohamad Salleh, Musdiana (2011)
This study aims to investigate the mediating effects of overall satisfaction on the relationship between relationship marketing and brand loyalty in the Islamic banking industry. Based on a sample of 268 customers and using statistical programming on social sciences approach, the three dimensions of relationship marketing; trust, commitment, and communication shkill are found to have positive effects on brand equity. Subsequently, trust and commitment were having a significant effect on Brand Familiarity, leaving Communication Skill to be insignificant towards brand familiarity. Finally, the relationship between Relationship Marketing and Brand Image, it proves that, only Commitment and Communication Skills were significant towards Brand Image and Trust has no significant impact on Brand Image. On the mediating effect of Overall Satisfaction on Brand equity, Brand familiarity, and Brand Image, Trust and commitment has a partial mediation on the relationship between relationship marketing and brand equity, while communication skills proves to have a full mediation on the same relationship. Following that, Trust and Commitment had a partial mediation effect on the relationship between Relationship Marketing and Brand Familiarity, and Communication skills has no mediation effect on the same relationship. Finally, on the relationship between Relationship Marketing and Brand Image, there was no mediation for communication skill and trust , follows by partial mediation for commitment. © 2011.